Bioluminescence in cephalopods: biodiversity, biogeography and research trends - Otjacques, Eve; Pissarra, Vasco; Bolstad, Kathrin; Xavier, José C.; McFall-Ngai, Margaret; Rosa, Rui (Frontiers in Marine Science, 2023)
Numerous terrestrial and marine organisms, including cephalopods, are capable of light emission. In addition to communication, bioluminescence is used for attraction and defense mechanisms. The present review aims to: (i) present updated information on the taxonomic diversity of luminous cephalopods and morphological features, (ii) describe large-scale biogeographic patterns, and (iii) show the research trends over the last 50 years on cephalopod bioluminescence. According to our database (834 species), 32% of all known cephalopod species can emit light, including oegopsid and myopsid squids, sepiolids, octopuses, and representatives of several other smaller orders (bathyteuthids, and the monotypic vampire “squid”, Vampyroteuthis infernalis and ram’s horn “squid”, Spirula spirula). Most species have a combination of photophores present in different locations, of which light organs on the head region are dominant, followed by photophores associated with the arms and tentacles and internal photophores. Regarding the biogeographic patterns of cephalopod species with light organs, the most diverse ocean is the Pacific Ocean, followed by the Atlantic and Indian Oceans. The least diverse are the Southern and the Arctic Oceans. Regarding publication trends, our systematic review revealed that, between 1971 and 2020, 277 peer-reviewed studies were published on bioluminescent cephalopods. Most research has been done on a single species, the Hawaiian bobtail squid Euprymna scolopes. The interest in this species is mostly due to its species-specific symbiotic relationship with the bacterium Vibrio fischeri, which is used as a model for the study of Eukaryote–Prokaryote symbiosis. Because there are many knowledge gaps about the biology and biogeography of light-producing cephalopods, new state-of-the-art techniques (e.g., eDNA for diversity research and monitoring) can help achieve a finer resolution on species’ distributions. Moreover, knowledge on the effects of climate change stressors on the bioluminescent processes is nonexistent. Future studies are needed to assess such impacts at different levels of biological organization, to describe the potential broad-scale biogeographic changes, and understand the implications for food web dynamics.